Classical and symmetrical horizontal convection: detaching plumes and oscillations. (10th June 2020) - Reiter, Philipp; Shishkina, Olga
Abstract : Abstract : Classical and symmetrical horizontal convection is studied by means of direct numerical simulations for Rayleigh numbers $Ra$ up to 3 × 10 12 and Prandtl numbers $Pr=0.1$, 1 and 10. For both set-ups, a very good agreement in global quantities with respect to heat and momentum transport is attained. Similar to Shishkina & Wagner ( Phys. Rev. Lett., vol. 116, 2016, 024302), we find Nusselt number $Nu$ versus $Ra$ scaling transitions in a region $10^{8}\leqslant Ra\leqslant 10^{11}$ . Above a critical $Ra$, the flow undergoes either a steady–oscillatory transition (small $Pr$ ) or a transition from steady state to a transient state with detaching plumes (large $Pr$ ). The onset of the oscillations takes place at $Ra\, Pr^{-1}≈ 5× 10^{9}$ and the onset of detaching plumes at $Ra\, Pr^{5/4}≈ 9× 10^{10}$ . These onsets coincide with the onsets of scaling transitions.